How Muslim Women in Jakarta Negotiate the ‘My Body, My Rules’ Narrative on Social Media: A Communication Perspective on Feminism and Islamic Values - Naya Adisti Prameswari Putrie; Feri Fahrianto; Rino Febrianno Boer; Ajif Yunizar Pratama (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2026)
A global wave of digital feminism has emerged, and the slogan “My Body, My Rules (abbreviated MBMR)” has spread widely across social platforms including TikTok and Instagram. However, after this discourse entered Indonesia’s Muslim communities, it required reinterpretation through integration with three core Islamic values: amanah, iffah, and maslahah, and the framing of bodily autonomy thus generated cross-cultural tensions. The author team of this paper centered their research on the core question of how Muslim women aged 20 to 40 in Jakarta negotiate and address this tension. Under a qualitative research framework, the study adopted a dual-path approach combining semi-structured interviews with digital discourse analysis. The study found that participants developed a form of negotiated agency, and that social media holds the dual attribute of being both an empowerment space and an arena for ideological contestation. This study supplements relevant research outcomes in the field of communication studies, proving that after localization, global feminist discourse can generate a hybrid agency that integrates individual empowerment and religious responsibility, and reshape the identity construction logic of contemporary digital communication.